Kekayaan Jenis Bulu Babi (Sea Urchin) di Kawasan Perairan Pantai Gunung Kidul, Yogyakarta - Prasetyo, Erik; Amalia Zaida, Amalia; Wulan, Intan Nawang; Wulandari, Retno; Santiati, Eny; Prakoso, Christopher Nicholas Yoshuaki (Universitas Jambi, 2019)
Gunung Kidul’s beaches haves several marine organism, one of that is sea urchin (Echinodermata). The objective of this research was to identify of sea urchins in Gunung Kidul’s beaches, Yogyakarta. The research of sea urchin in Gunung Kidul’s beaches was conducted from April to May 2018 located in Drini Beach, Ngrenehan Beach, and Widodaren Beach. The data was collected using 1m x 1m square-transect method. The result showed there were 7 (seven) species of sea urchins belonging to 4 (four) families and 3 (three) orders. The most numberous of sea urchins (six species) found in Widodaren Beach that were Echinometra sp., Echinometra mathaei, Heterocentrotus sp., Tripneustes ventricosus, Colobocentrotus atratus, and Arbacia lixula. Meanwhile in Drini Beach and Ngrenehan Beach was only found each 4 (four) species, that were Echinometra sp., Echinometra mathaei, Heterocentrotus sp., and Stomopneustes variolaris.